Lymphoscintigraphy with peritumoral injection versus lymphoscintigraphy with subdermal periareolar injection of technetium-labeled human albumin to identify sentinel lymph nodes in breast cancer patients. (February 2014) - Caruso, Giuseppe; Cipolla, Calogero; Costa, Renato; Morabito, Alessandra; Latteri, Stefania; Fricano, Salvatore; Salerno, Sergio; Latteri, Mario Adelfio
Background: Preoperative lymphoscintigraphy is without doubt a valid method for the detection of the sentinel lymph node (SLN). There has been considerable debate regarding the optimal site for the introduction of the tracer; various sites include peritumoral (PT), periareolar (PA), subdermal, and intradermal injection. Purpose: To evaluate retrospectively the lymphoscintigraphic identification rate of peritumoral (PT) injection versus subdermal periareolar (PA) injection in the detection of SLNs in breast cancer. Material and Methods: Between October 2002 and December 2011, a cohort of 906 consecutive patients with biopsy proven breast cancer underwent 914 SLN biopsy procedures. A total of 339 procedures (Group A) were performed using a PT deep injection of radiotracer while 575 procedures (Group B) adopted a subdermal PA injection of radiotracer towards the upper outer quadrant, regardless of the site of the carcinoma. All the patients underwent synchronous excision of the breast cancer and SLN biopsy. Results: SLNs were identified in the lymphoscintigram in 308/339 cases (90.85%) of Group A (PT injection) and in 537/575 cases (93.39%) of Group B (PA injection). Furthermore, in 2/339 patients (0.58%) of Group A, internal mammary lymph nodes were found at lymphoscintigraphy, whereas no internal mammary sentinel nodes were found in the Group B patients. The intraoperative identification rate of axillary SLNs was 99.41% (337 of 339) in the Group A patients and 99.65% (573 of 575) in the Group B patients. There was no significant difference in the two groups between the incidence of the number of SLNs detected and the incidence of identification of positive SLNs. Conclusion: PT versus PA injection of radiotracer showed comparable success rates for axillary SLN identification, and can be considered a rapid and reliable method.